Pengembangan Model Simulasi Kebijakan Pengelolaan Ikan Berkelanjutan - Ratna Purwaningsih; Sjarief Widjaja; Sri Gunani Partiwi (Institute of Research and Community Outreach - Petra Christian University, 2012)
Stock assessment studies of Sardinella Lemuru Bali strait indicate overfishing. The growth of fishing vessel numbers result on fish biomass stock reduction. Sustainable fishery management in overfishing area can be done by limiting number of fishing effort. There are three kinds of methods approach on determine number of fishing effort and total allowed catch (1) Maximum Sustainable Yield (MSY), (2) Maximum Economic Yield (MEY) and (3)Maximum Social Yield (MScY). Sustainable fishery has three main aspect as its indicators; ecology, economic and social. This research attempts to simulate three kinds of methods to the indicators of sustainable fishery (1) biomass fish stock as ecological aspect, (2) profit of purse seine fishing vessel as economical aspect and (3) numbers of fishers involved in the business of marine capture fishery represents social aspect. System dynamic method and powersim software are used in simulation model. Simulation output shows that fish biomass stock can be maintain in sustainable level by applied fishery policy. Limiting number of fishing effort create balancing between fish stock natural growth and fish harvest. This policy starts to apply on year 2010 in simulation model and run until 2030 to forecast future condition of fish biomass stock.